Impact of intrathecal cell therapy with autologous stromal cells on short‐term memory binding in early Alzheimer's disease: One‐year follow‐up assessment: Human/Human trials: Other. (7th December 2020) - Guinea, Sara Fernández; Zurita, Mercedes; Mucientes, Jorge; García, Estefanía; Marqués, Javier González; Parra, Mario A.; Vaquero, Jesús
Abstract: Background: We had previously reported that the administration of autologous stromal cells (ASCs) therapy to two patients with mild AD dementia led to a global increase in cerebral glucose metabolism which was accompanied by significant improvement of visual short‐term memory binding (VSTMB), a function known to be a marker of AD. We suggested that intrathecal administration of autologous ASCs could be considered a new therapeutic strategy for AD dementia (Vaquero et al., 2019). We were interested in investigating the post‐intervention durability of such cognitive improvements. Methods: We studied two AD patients with cerebral beta‐amyloid neuritic plaques detected with 18FFDG‐PET. The patients received every three months 100 million of ASCs by intrathecal route, until a total dose of 300 million. None received any other medication for its disease at the time of receiving cell therapy. Clinical and neuroimaging studies were performed previous and after the therapy, including brain glucose metabolism by 18F‐FDG‐PET and assessment with the visual short‐term memory binding task (VSTMBT). This task has been proposed as a preclinical marker of AD. It requires subjects to detect whether or not two combinations of shape and colour change across two sequential arrays. Here we report on the assessment of these patients one year after the therapy. We compared them with 4 AD patients who did no undergo stem cell therapy. Results: Single case statistics revealed that benefits drawn by treated patients from the therapy remained a year after. Using a more taxing version of the VSTMB test (memory load of 3 items) we observed that, after the therapy, the chance that an untreated AD patient would show more impairment was 75.45% (p= 0.24) for Case 1 and 89.23% (p=0.11) for case 2. This chance remained after 1 year post‐treatment for Case 1 (75.45%, p=0.24) and increased for Case 2 (96.89%, p=0.031). Conclusion: Improvements of memory functions known to be marker for AD in patients who underwent stem cell therapy remained stable after one year post‐intervention. This offers a new therapeutic strategy for AD.